Evaluation of Antidiabetic Activity of Sargassum tenerrimum in Streptozotocin-Induced Diabetic Mice - A. Philomena Joy Lindsey; Reya Issac; M. Lakshmi Prabha; R. Emilin Renitta; Angeline Catherine; Antony V. Samrot; S. Abirami; P. Prakash; S. Dhiva (Journal of Pure and Applied Microbiology, 2021)
Diabetes mellitus has become the most predominant disease in most of the developing and developed countries. Diabetes could occur at any stage of life for which a change in sedentary life style is the possible solution. Despite the introduction of several medications, to curtail the side effects associated with diabetes mellitus, there is no medication or treatment for complete cure. Existing medications and treatments are targeted to mitigate the intensity of the disease which abruptly could result in organ failure. Rather than the available types of treatments, natural medication is reported to produce commendable results. Extracts of many medicinal plants and seaweeds have been documented to possess anti-diabetic properties. A brown alga, S. tenerrimum, found on the west coast of India, is chosen in this study to analyse the anti-diabetic property of its methanolic extract. This extract was used to treat streptozotocin-induced diabetic mice. An experimental design was framed based on acute toxicity studies to determine the change in blood glucose level, body weight, lipid profile, liver enzymes (SGPT and SGOT) and the renal function markers (urea and creatinine). After 15 days of treatment, an increase in body weight and HDL cholesterol was observed while the total cholesterol, VLDL, LDL, serum triglyceride, SGOT, SGPT, creatinine and urea decreased with 250 mg/Kg.bw of S. tenerrimum methanolic extract in Streptozotocin-induced diabetic mice group. This difference is significant (p<0.05) when compared with a healthy non-diabetic mice group and a treated diabetic mice group. This proves that the methanolic extract of S. tenerrimum possess anti-diabetic property. Further research could explore the active compounds that can be used in the formulation of herbal medicine for diabetes mellitus.